Theoretical finishing size limitation and failure mechanism of viscoelastic abrasive media on micro-hole structure - Baocai Zhang; Xiayu Wang; Neng Jiang; Jun Tang; Fanghong Sun; Xinchang Wang (Journal of Materials Research and Technology)
Owing to the restriction of micro dimension size and multiple holes, traditional finishing processes exhibits inevitable finishing limitations, hence abrasive flow machining is employed to break above limitations relying on the unique viscoelasticity and excellent fluidity of abrasive media. However, as the primary requirement of media is the material removal, there must be a limitation size when the micro hole reducing to a critical value since the rigid grains should be added and must hold an apparent dimension. In present paper, the structures and rheology of media are systematically investigated to subsequently elaborate the finishing mechanism on micro-hole structures. Furthermore, based on the pseudo-network structure and elasticity of media, as well as the interaction between continuous matrix with discrete grains, this work theoretically established the mechanics model on single grain and the total material removal model to discussed the variation tendency of material loss volume along with the key parameters (storage modulus, inlet pressure, non-Newtonian index and grain fraction), primarily detecting the theoretical size limitation (around 5 μm). Moreover, further considering the influence of thermal accumulation and grain abrasion on the properties and final effect of media under long finishing duration state, the failure mechanism of abrasive media was investigated and concluded as the deterioration of rheological properties, violent abrasion of grain, and rather low mechanical performance gap between rigid grains with target surface. This work could give a guidance on the determination of adaptable size range and longevity of abrasive media when finishing the micro-hole structures.